Review of Integration of theory and practice in CLIL - Ramos, Lucilene Ongaratto (BELT - Brazilian English Language Teaching Journal, 2014)
Content and Language Integrated Learning (CLIL) has now become a feature of education in Europe from primary school to university. This method has been used in programs in order to challenge teachers to integrate language learning with content learning, that is, to explore different areas of the curriculum such geography, history, art, among others, using an additional language as the language of instruction. CLIL classrooms use a foreign language to teach their contents and, additionally, students have language classes in order to improve learning. Then, they are going to be able to develop better learning strategies to understand the contents that are being taught in a language that is not their mother tongue.